Toxicity of high-purity silver nanoparticles to the aquatic plant Lemna minor : - Μηνόγιαννης, Παναγιώτης (2015)
The increasing penetration of nano-products to the market is raising big concerns about their potential toxic and environmental effects of their constituent engineered nanoparticles (ENPs). The contradictory toxicity test results reported in the literature thus far can be explained by differences in the ENP production methods, which can strongly affect nanoparticle purity and therefore the outcome of the tests. In this paper we investigate the toxicity of Ag nanoparticles (AgNPs) produced by spark ablation, a gas-phase technique that can deliver well-defined nanoparticles of extremely high purity, on Lemna minor. Our results show that AgNPs exhibit a toxic behavior at concentrations as low as 5 μg L-1, which is considerably lower compared to the threshold concentrations reported in other studies. This difference can be attributed to the high purity of the ENPs used in our measurements, which can release higher concentrations of toxic Ag+ ions upon dilution in the test solution.